Preparation, characterization and evaluation of the in vivo trypanocidal activity of ursolic acid-loaded solid dispersion with poloxamer 407 and sodium caprate - Josimar Oliveira Eloy; Juliana Saraiva; Sérgio de Albuquerque; Juliana Maldonado Marchetti (Universidade de São Paulo, 2015)
Ursolic acid is a promising candidate for treatment of Chagas disease; however it has low aqueous solubility and intestinal absorption, which are both limiting factors for bioavailability. Among the strategies to enhance the solubility and dissolution of lipophilic drugs, solid dispersions are growing in popularity. In this study, we employed a mixture of the surfactants poloxamer 407 with sodium caprate to produce a solid dispersion containing ursolic acid aimed at enhancing both drug dissolution and in vivo trypanocidal activity. Compared to the physical mixture, the solid dispersion presented higher bulk density and smaller particle size. Fourier Transform Infrared Spectroscopy results showed hydrogen bonding intermolecular interactions between drug and poloxamer 407. X-ray diffractometry experiments revealed the conversion of the drug from its crystalline form to a more soluble amorphous structure. Consequently, the solubility of ursolic acid in the solid dispersion was increased and the drug dissolved in a fast and complete manner. Taken together with the oral absorption-enhancing property of sodium caprate, these results explained the increase of the in vivo trypanocidal activity of ursolic acid in solid dispersion, which also proved to be safe by cytotoxicity evaluation using the LLC-MK2 cell line.